Āśvalāyana sandhyopāsana prayogaḥ : Āndhrapaddhatiḥ - Sivaramakrishnayya, Parasaram N. (P.N. Sivaramakrishnayya : Copies can be had of K.S. Rajagopala Iyer, 1980)
Manual of the Hindu daily rite Sandhyā, according to the Āśvalayana school of the Rgveda and worship of various Hindu deities.